[Three-Year Strategic Plan - Fire Safety Issue] (Tufts Archival Research Center, 2007)
Draft; Confidential; Three-year strategic plan for fire safety issue. Provides background and assumptions, focusing on likely federal activity regarding fire-safe cigarettes. Lists organizations and individuals of political importance, including key members of Congress, regulatory agencies, national fire service organizations (supportive and non-supportive), and related organizations. Also lists key states, primarily industrial and metropolitan states in the Northeast, North Midwest, and West. Cites objective as helping fire service reduce incidence and severity of accidental fires and increasing awareness among fire service and key public officials of industry work to reduce accidental fires. Concludes with detailed strategies and tactics for working with identified politically important organizations and individuals.